Análise das condições favoráveis para a inovação e seus resultados nas empresas residentes em parques tecnológicos - Roldan, Lucas Bonacina (2016)
The growing competition is causing companies to create innovations to excel in an environment of uncertainties. In that context, companies that operate in isolation usually do not have access to specialized resources, and as an alternative to such difficulties, technology parks arise as the solution for that problem. Technology parks are environments that offer conditions for the innovation to develop, and companies settled within them are able to take advantage of its structure, thus generating competitive advantages. Many public policies around the world are prioritizing the development of those kind of technology parks, causing the issue to deserve a better understanding. Due to the complexity of those parks, it is important to understand how innovation occurs within those innovation ecosystems, and how the innovations affect the performance of the companies. Many studies have addressed this issue; however, most of times it is dealt qualitatively, or through secondary data, thus needing further elaboration. Given that, the present study aimed to analyze the relationship between innovation-friendly conditions in the technology parks, the innovations made by the companies settled within them, and their results in terms of organizational performance. To develop this model, a literature search was first conducted, in order to list the possible restrictions of innovation in technology parks, the innovations and their results in terms of business performance. Later, a qualitative phase was conducted comprising six managers of technology parks, in order to verify whether the literature presuppositions were appropriate to the Brazilian context, and to carry out such adaptation and consolidate the theoretical model; and finally, a quantitative study was carried out (comprising one hundred ninety-two companies settled in parks) to test the model developed through structural equation modeling. As results, first, constructs were proposed to measure the favorable conditions for innovation in technology parks and, the theoretical model was checked in cooperation with technology parks experts. After that, the assumptions of the theoretical model were tested through structural equation modeling, and it was identified that the innovations are positively influenced by support services (innovation and marketing process), as well as by the physical infrastructure (product, process, organization and marketing innovation); however, the relationship network among the companies negatively influence the innovation process, being the latter result not in accordance with the premises of the literature on technological parks, implying further insights on this issue. Another result was that the process innovations and marketing positively influence the performance of companies settled within the technological parks, which is in accordance with the innovation literature, demonstrating that effectively parks contribute to innovation in resident companies.